2015 SCAI/ACC/HFSA/STS clinical expert consensus statement on the use of percutaneous mechanical circulatory support devices in Cardiovascular Care (Endorsed by the American heart association, the Cardiological society of India, and Sociedad Latino Americana de Cardiología Intervencionista; Affirmation of value by the Canadian association of interventional Cardiology–association Canadienne de Cardiologie d'intervention)1. Issue 7 (7th April 2015) - Rihal, Charanjit S.; Naidu, Srihari S.; Givertz, Michael M.; Szeto, Wilson Y.; Burke, James A.; Kapur, Navin K.; Kern, Morton; Garratt, Kirk N.; Goldstein, James A.; Dimas, Vivian; Tu, Thomas; From the Society for Cardiovascular Angiography; et al.
<x xml:space="preserve">Abstract</x> This article provides a brief summary of the relevant recommendations and references related to percutaneous mechanical circulatory support. The goal was to provide the clinician with concise, evidence‐based contemporary recommendations, and the supporting documentation to encourage their application. The full text includes disclosure of all relevant relationships with industry for each writing committee member. A fundamental aspect of all expert consensus statements is that these carefully developed, evidence‐based documents can neither encompass all clinical circumstances, nor replace the judgment of individual physicians in management of each patient. The science of medicine is rooted in evidence, and the art of medicine is based on the application of this evidence to the individual patient. This expert consensus statement has adhered to these principles for optimal management of patients requiring percutaneous mechanical circulatory support. © 2015 by The Society for Cardiovascular Angiography and Interventions, The American College of Cardiology Foundation, the Heart Failure Society of America, and The Society of Thoracic Surgeons.